Therapeutic strategies to fight COVID‐19: Which is the status artis? - Scavone, Cristina (Br J Pharmacol, 2021)
COVID‐19 is a complex disease, and many difficulties are faced today especially in the proper choice of pharmacological treatments. The role of antiviral agents for COVID‐19 is still being investigated and evidence for immunomodulatory and anti‐inflammatory drugs is quite conflicting, whereas the use of corticosteroids is supported by robust evidence. The use of heparins in hospitalized critically ill patients is preferred over other anticoagulants. There are conflicting data on the use of convalescent plasma and vitamin D. According to the World Health Organization (WHO), many vaccines are in Phase III clinical trials, and some of them have already received marketing approval in European countries and in the United States. In conclusion, drug repurposing has represented the main approach recently used in the treatment of patients with COVID‐19. At this moment, analysis of efficacy and safety data of drugs and vaccines used in real‐life context is strongly needed. LINKED ARTICLES: This article is part of a themed issue on The second wave: are we any closer to efficacious pharmacotherapy for COVID 19? (BJP 75th Anniversary). To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v179.10/issuetoc